PENGEMBANGAN SISTEM COMPUTER ADAPTIVE TEST (CAT) DENGAN PENDEKATAN ITEM RESPONSE THEORY (IRT) - Firdaus Firdaus; Asrul Huda; Dedy Irfan; Yeka Hebdriyani (EDUTECH, 2022)
This study aims to produce a Computer Adaptive (CAT) system with an Items Response Theory (IRT) approach in Multimedia for Students of SMK Negeri 1 Gunung Talang. This research is a research on the development of a web-based system using the RD (Research and Development) method by applying the 4-D (Four-D) models. Basically this system is almost the same as the CBT (Computer Based Test) system, the difference from this system is that the system is able to randomize and give questions according to the ability of the test takers by using the Items Response Theory (IRT) algorithm. This system uses the Items Response Theory 3-PL model in which the parameters of this model are the level of difficulty of the items, the discriminating power of the questions and the questioning or distraction. This test system will give questions randomly to students based on the test takers' responses to the previous questions, In this system, each test taker will never get the same order of questions. Termination of the test when the test taker has reached the level of accuracy of the ability estimate, namely SE = 0.01 or if the items have been exhausted. The result of this research is a Computer Adaptive Test (CAT) system with an Items Response Theory (IRT) approach, which can be used in the process of assessing student learning outcomes. The implementation of this research is applied in the Multimedia Department of SMK Negeri 1 Gunung Talang with Printing Graphic Design Subjects.